The Role of the General Elections Supervisory Agency's Communication in Overseeing Election Campaigns and Preventing Violations in Aceh Tamiang Regency - Akbar, Panji; Rudianto, Rudianto; Priadi, Ribut (Persepsi: Communication Journal, 2024)
This study aims to determine the communication role of the commissioner of the General Election Supervisory Agency in supervising clean election campaigns and preventing campaign violations in Aceh Tamiang Regency. The election supervisory body as an institution that has the task of supervising the course of elections has a very important role for the creation of elections with the slogans of direct, public, free, secret, honest and fair. This study uses a qualitative approach by combining in-depth interviews, and observations. This research uses interpersonal communication theory and also political communication theory. The results of this study revealed that the role of communication carried out by the Aceh Tamiang Regency Bawaslu is to socialize, coordinate and also give appeals. By carrying out communication roles such as socialization with the ranks at the sub-district level, stakeholders, as well as political parties, coordination and also giving appeals, it is very important to provide understanding and information that you want to convey to the communicator (the person who receives the message).  In addition, the communication role of the Bawaslu Commissioner in efforts to prevent campaign violations, among others, is to emphasize persuasive communication in order to minimize the occurrence of election campaign violations. All of these roles have been carried out by the Aceh Tamiang Regency Bawaslu in order to oversee clean election campaigns and prevent election violations in the Aceh Tamiang Regency area.